EVALUASI PENGGUNAAN LAHAN DAERAH RUMPIN DAN SEKITARNYA, KAB. BOGOR, JAWA BARAT - Himmes Fitra Yuda; Suherman Dwi Nuryana; Novi Triany; Eddy Sugiarto; M. Adimas Amri (Universitas Negeri Padang, 2022)
Rumpin sub-district is an area in the northwest part of the capital city of Jakarta which is included in the division of West Bogor Regency. The potential and resources possessed are the main reasons for the new city development plan to be carried out in the region. This study aims to provide information related to regional development planning based on environmental geology. The research method is taking geological, hydrological, disaster and current land use data as well as collecting secondary data obtained from data guardians or related agencies to support the data with the final result in the form of recommendation maps and evaluation of land use in the research area carried out by scoring. quantitatively and assessment of overlapping (overlay) SKL maps using mapping software. The results showed that the study area had a moderate-good soil bearing capacity, a poor grade of sandy soil, three classes of slopes, namely flat-sloping (0-15%), moderately steep (15-25%) and steep-very steep (> 25%). Based on the availability and productivity of aquifers, they are divided into two units, namely local, medium-production aquifers and areas of scarce groundwater. The disaster factor is soil movement from the Land Movement Vulnerability Zone Map showing that the Rumpin area is included in the Low to Medium Ground Movement. The results of the weighting of the research area are divided into three regional recommendations, namely good, medium and bad, and an evaluation of land use is carried out with the current land use map region.